Multi-class idiopathic scoliosis detection based on Cobb angle using a hybrid ViT model - Yesilmen, Nevzat; Baydogan, Merve Parlak; Danaci, Cagla; Tuncer, Seda Arslan; Cinar, Ahmet; Tuncer, Taner (Springer London Ltd, 2025)
Idiopathic scoliosis can significantly negatively affect the individual's quality of life and cause physical and psychological problems. The first step in the treatment process of the disease is to determine the Cobb angle. Alternative treatment methods such as brace treatment, physical therapy and exercise, surgical intervention, only follow-up or acupuncture can be applied to the patient according to the Cobb angle. Therefore, the Cobb angle plays a critical role in determining the treatment method to be applied to the patient. In this study, a hybrid ViT model that can perform multi-class scoliosis classification according to the Cobb angle from X-ray images was proposed. The proposed model uses ViT Base Patch16 and ViT Base Patch32 models to obtain both micro- and macro-scale structural information in X-ray images. Classification was performed with machine learning algorithms by combining the feature maps obtained from both models. 93.80% accuracy and 99.63% AUC values were obtained with the logistic regression classifier.
Keywords: Idiopathic scoliosis; Vision transformer; Cobb angle; Classification